Investigation on thermal characteristics and desensitization mechanism of improved step ladder-structured nitrocellulose - Cheng-kai Pu; Yu Luan; Ming-jun Yi; Zheng-gang Xiao (Defence Technology, 2023)
Nitrocellulose, or cellulose nitrate, has received considerable interest due to its various applications, such as propellants, coating agents and gas generators. However, its high mechanical sensitivity caused many accidents during its storage and usage in ammunition. In this work, two kinds of insensitive step ladder-structured nitrocellulose (LNC) with different nitrogen contents were synthesized. The products were characterized by FT-IR, Raman, XRD, SEM, elemental analysis, TGA, DSC, accelerating rate calorimeter analysis (ARC), and drop weight test to study their molecular structure, thermal characteristics and desensitization performance. Compared with raw nitrocellulose, LNC has a sharper exothermic peak in the DSC and ARC curves. The H50 values of the two kinds of LNC increased from 25.76 to 30.01 cm for low nitrogen content and from 18.02 to 21.84 cm for high nitrogen content, respectively. The results show that the ladder-structure of LNC which provides regular molecular arrangement and a soft buffer made with polyethylene glycol could affect the energy releasing process of LNC and reduce the sensitivity of LNC. Insensitive LNC provides an alternative to be used as a binder in insensitive propellants formulation.